Determination of Purchase Decision: Product Quality, Price and Place (Literature Review) - Prihartono, Prihartono (Dinasti Publisher, 2021)
The Literature Review Article Determination of Purchase Decision: Product Quality, Price and Place is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Product Quality is related to Purchase Decisions; 2) Price relates to Purchase Decision; and 3) Place related to Purchase Decision. Apart from these 3 exogenous variables that affect the endogenous variable of Purchase Decision, there are still many other factors including service quality, product design and promotion variables.